Biometric Relationship Between Growth Pattern and Biological Reproduction of a Living Fossil Benthic Brachiopods (Lingula anatina Lamarck, 1801) in Aceh Northern Shore - Octavina, Chitra; Irsad, Muhammad; Al-Ihsan, Muhammad Tareqh; Niwatana, Julya; Ulfah, Maria; Nurfadillah, Nurfadillah; Agustina, Sri; Nur, Firman Muhammad; Anh, Nguyen Thi Mai (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2023)
Brachiopods are a group of ancient marine invertebrates that are still found today, so they are known as "living-fossil". The purpose of this study was to determine reproductive biology through sex ratio approach, gonad maturity stages, body mass weight and growth pattern of L. anatina through size distribution approach, length-weight relationship, and condition factors. This research was conducted from April to December 2021, at the Aceh northern shore. The method used in this research is purposive sampling. The results showed that based on the morphological characteristics, only one species of brachiopods from the class Lingulata was found, namely Lingula anatina Lamarck, 1801. This species has an unequal sex ratio. Analysis of Body Mass Weight (BMW) and Gonado Somatic Index (GSI) shows an inverse relationship where the BMW value is lower than the GSI value. The condition factor of L. anatina also fluctuates every month, this is presumably due to availability of food in habitat. Gonad maturity stages of L. anatina at the locations of Syiah Kuala and Alue Naga were in spawning conditions (stages IV), especially for female L. anatina. These results indicate that the reproductive quality of L. anatina at the Aceh northern shore was maintained due to minimal exploitation from the surrounding community. Furthermore, the biometric (length – weight relationship) of L. anatina in the Aceh northern shore showing an isometric and negative allometric pattern. Basically, allometric growth is temporary, for example due to changes related to gonadal maturity, while isometric growth is a continuous change that is proportional.